EFFECTIVENESS OF POLICY IMPLEMETATION ON INTEGRATED ENTREPRENEURSHIP DEVELOPMENT PROGRAM IN PASAR MINGGU DISTRICT - Deddy Herlisyah; Yulianto (Adisam Publisher, 2023)
The implementation of the Integrated Entrepreneurship Development Program (PKT) policy in Pasar Minggu District, South Jakarta Administration City has not been able to provide appropriate and accurate services in facilitating existing MSMEs and the ability of the mentoring team is still lacking to help the community and program recipients appropriately and respond to their problems, as well as informing the appropriate method/method of assistance provided according to the problem cases of the program participants. The purpose of this study is to analyze the effectiveness of Integrated Entrepreneurship Development Program (PKT) Policy Implementation in Pasar Minggu District, South Jakarta Administration City. The research is a case study method with data collection techniques using interviews, document review and observation. Interviews were conducted on 5 (five) key informants, reviewing documents on documents related to research. The data analysis technique uses data reduction, data presentation and conclusion drawing. Test the validity of the data by testing the criteria, namely credibility, transferability, dependability, and confirmability. The results showed that the effectiveness of the Integrated Entrepreneurship Development Program (PKT) Policy Implementation in Pasar Minggu District, South Jakarta Administration City was still low, due to the implementation of the Integrated Entrepreneurship Development Program (PKT) in Pasar Minggu District in terms of the accuracy of program targets, aspects of program socialization, aspects of program objectives and aspects of program monitoring.